Using Personal Vocabulary Notes (PVN) Technique to Develop the Students Vocabulary - Awalia, Awalia (Maspul Journal of English Studies, 2021)
The purpose of this study is: To find out whether Personal Vocabulary Notes (PVN) can increase student vocabulary in Papi Enrekang MTs. The method used in this study is a quantitative method and research design is a pre-experimental study. The sampling technique used in this study is cluster sampling. Researchers took one class as the subject of this study. Researchers have compiled the pretest score before treatment is provided and after treatment is provided. The results obtained are statistical analysis for 0.05 significance level with degrees of freedom (DF) = N-1, where (n) = 21, DF = 17. The probability value is smaller than